Tip - erotic short story - Olesen, Anne-Marie Vedsø (Saga Egmont, 2022)
Tip started licking her clitoris. Sweet, unbearable rushes coursed through her quivering spleen. Everything trembled. She consisted only of desire, it was as if nothing existed but her tongue and her impatient, hungry body." Merete met Tip before she was to take part in a debate against prostitution. Afterwards she couldn't stop thinking about him. Without really knowing how it happened, she lied to her husband about where she was going and ended up at Tip's who gave her a satisfactory reception